P155 Safety of tiotropium respimat® add-on therapy in patients aged 6–17 years with symptomatic asthma. (15th November 2016) - Vogelberg, C; Szefler, SJ; Hamelmann, E; Boner, A; Moroni-Zentgraf, P; Engel, M; Azzi, G El; Finnigan, H; Vandewalker, M
Abstract : Introduction and objectives: Two Phase II trials have shown tiotropium Respimat® (tioR) to be a well-tolerated bronchodilator in patients aged 12–17 1 and 6–11 2 years with symptomatic asthma. Here, we further assessed the safety and tolerability of once-daily (QD) tioR add-on therapy in Phase III trials in patients aged 6–17 years with symptomatic asthma. Methods: Data was analysed from three completed Phase III, randomised, double-blind, placebo-controlled, parallel-group trials: VivaTinA (NCT01634152 ), 12-week trial, patients aged 6–11 years; PensieTinA (NCT01277523 ), 12-week trial, patients aged 12–17 years; RubaTinA (NCT01257230 ), 48-week trial, patients aged 12–17 years. Patients received QD tioR 5 μg (2 puffs, 2.5 µg), QD tioR 2.5 μg (2 puffs, 1.25 µg) or QD placebo Respimat® (pboR; 2 puffs) as add-on to background therapy. Adverse events (AEs) were recorded and analysed descriptively by age: 6–11 years; 12–17 years. Results: 1189 patients were treated: 6–11 years, n = 400; 12–17 years, n = 789. The frequency of patients with AEs was similar across all treatment arms, with a low incidence of drug-related and serious AEs; asthma and decreased peak expiratory flow rate were the most common AEs (Table). No deaths occurred. Conclusion: The AE profile and AE incidences were similar between tioR 5 µg, tioR 2.5 µg and pboR, as add-on to inhaled corticosteroid ± other controllers, in patients aged 6–17 years with symptomatic asthma. References: Vogelberg C, et al . Respir Med 2014;108 :1268–76. Vogelberg C, et al . Respir Res 2015;16 :20.